Comparison of the pharmacokinetics between L-BPA and L-FBPA using the same administration dose and protocol: a validation study for the theranostic approach using [18F]-L-FBPA positron emission tomography in boron neutron capture therapy. Issue 1 (December 2016) - Watanabe, Tsubasa; Hattori, Yoshihide; Ohta, Youichiro; Ishimura, Miki; Nakagawa, Yosuke; Sanada, Yu; Tanaka, Hiroki; Fukutani, Satoshi; Masunaga, Shin-ichiro; Hiraoka, Masahiro; Ono, Koji; Suzuki, Minoru; et al.
Abstract Background Boron neutron capture therapy (BNCT) is a cellular-level particle radiation therapy that combines the selective delivery of boron compounds to tumour tissue with neutron irradiation. L-p -Boronophenylalanine (L-BPA) is a boron compound now widely used in clinical situations. Determination of the boron distribution is required for successful BNCT prior to neutron irradiation. Thus, positron emission tomography with [18 F]-L-FBPA, an18 F-labelled radiopharmaceutical analogue of L-BPA, was developed. However, several differences between L-BPA and [18 F]-L-FBPA have been highlighted, including the different injection doses and administration protocols. The purpose of this study was to clarify the equivalence between L-BPA and [19 F]-L-FBPA as alternatives to [18 F]-L-FBPA. Methods SCC-VII was subcutaneously inoculated into the legs of C3H/He mice. The same dose of L-BPA or [19 F]-L-FBPA was subcutaneously injected. The time courses of the boron concentrations in blood, tumour tissue, and normal tissue were compared between the groups. Next, we administered the therapeutic dose of L-BPA or the same dose of [19 F]-L-FBPA by continuous infusion and compared the effects of the administration protocol on boron accumulation in tissues. Results There were no differences between L-BPA and [19 F]-L-FBPA in the transition of boron concentrations in blood, tumour tissue, and normal tissue using the same administration protocol. However, the normal tissue to blood ratio of the boron concentrations in the continuous-infusion group was lower than that in the subcutaneous injection group. Conclusions No difference was noted in the time course of the boron concentrations in tumour tissue and normal tissues between L-BPA and [19 F]-L-FBPA. However, the administration protocol had effects on the normal tissue to blood ratio of the boron concentration. In estimating the BNCT dose in normal tissue by positron emission tomography (PET), we should consider the possible overestimation of the normal tissue to blood ratio of the boron concentrations derived from the values measured by PET on dose calculation.